1949
DOI: 10.1084/jem.89.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of the Host and Natural Resistance to Infection

Abstract: The double strain inoculation (DSI) method of testing for natural resistance to infection has been examined in the instance of mouse salmonellosis. The DSI method has been found capable of detecting differences in natural resistance due to genetic as well as nutritional causes. A difference in response to Salmonella infection was found for the first time between the two "susceptible" inbred mouse strains, BSVR and BSVS. Whereas BSVS mice for the most part survived an intraperitoneal injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1956
1956
1966
1966

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the present investigation we have elected the genetic arrangement of host differences in survivorship. Now, although the physiological mechanism responsible for such genetically arranged differences is unknown it has been shown that these very survivorship differences are operationally dependent on the genetic structure of the pathogen population, demanding a genetic heterogeneity in terms of virulence (6). It is still moot whether this operational necessity can be generalized to embrace other infectious diseases, but in the present concern with mouse salmonellosis we have felt obliged to retain this prescription and have employed the double strain inoculation infection test (7) as a precise means of providing the appropriate pathogen populational structure.…”
mentioning
confidence: 99%
“…In the present investigation we have elected the genetic arrangement of host differences in survivorship. Now, although the physiological mechanism responsible for such genetically arranged differences is unknown it has been shown that these very survivorship differences are operationally dependent on the genetic structure of the pathogen population, demanding a genetic heterogeneity in terms of virulence (6). It is still moot whether this operational necessity can be generalized to embrace other infectious diseases, but in the present concern with mouse salmonellosis we have felt obliged to retain this prescription and have employed the double strain inoculation infection test (7) as a precise means of providing the appropriate pathogen populational structure.…”
mentioning
confidence: 99%